(untitled) (Universal International Scientific Journal, 2026)
This article comprehensively analyzes the compositional and artistic functions of the landscape image in the stories of the famous Russian writer K. G. Paustovsky. The study highlights the role of the landscape in the construction of the plot, the psyche of the hero, the author’s idea, and the philosophical content of the work. It is substantiated on the basis of scientific evidence that the image of nature in Paustovsky’s work is not only a background for events, but also an active element of epic thinking.